Efektivitas Kamar Ultraviolet Germicidal Irradiation (UVGI) Rumah Sakit Cipto Mangunkusumo untuk Disinfeksi Respirator N95 di Pandemi COVID-19: Studi Pendahuluan - Ratna Dwi Restuti; Harim Priyono; Rangga Rayendra Saleh; Ayu Astria Sriyana; Prasandhya Astagiri Yusuf; Tri Juda Airlangga; Ari Prayitno; Gortap Sitohang; Fitri Arman; Suko Dwi Priyanto (Majalah Kedokteran Indonesia, 2022)
Introduction: During the COVID-19 pandemic, where the disease might spread in a medical facility setting, the common problems found in every country is the shortage of personal protective equipment (PPE) for medical personnel – especially the disposable N95 respirators. Thus, a higher amplitude to disinfect and reuse N95 is urgently needed. In this study, we designed an effective and safe disinfection methods through an Ultraviolet Germicidal Irradiation (UVGI) chamber in Dr. Cipto Mangunkusumo Hospital to control the shortage of PPE by disinfecting and reusing disposable N95 respirators. Purpose: To evaluate the dosage and effectiveness of UV-C radiation for disposable N95 respirators disinfection in our designated UVGI chamber. Methods: This study used a cross-sectional design to determine the dose and the effectiveness of UV-C radiation in eradicating SARS-CoV 2 on disposable N95 respirators. Results: Using two different distances from the light source, we confirmed the inverse square law of UV-C radiation power. Irradiation for 2 hours with a radiation dose of 1080 mJ/cm2 resulted in undetected SARS-CoV-2 gene based on PCR examination in 10 out of 10 samples. Conclusion: This UVGI chamber is a potential solution for hospitals or medical facilities to overcome the limitations that occurred in the pandemic by disinfecting PPE.